PENGARUH DUKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA MAS THAWALIB PARABEK - Duwik Yulistia; Yeni Afrida; M. Arif; Sri Hartati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to determine the extent of peer support influence on the academic achievement of eleventh-grade IPS students at MAS Sumatera Thawalib Parabek. This study uses a quantitative approach with the type of regression. The population in this study is 246 students. However, the researcher only took a sample from the eleventh-grade IPS students. The sampling technique used is total sampling, meaning all eleventh-grade IPS students were taken as 45 samples. The data collection technique in this study is a questionnaire about peer support and academic achievement data. To evaluate the research hypothesis, data analysis techniques such as simple linear regression were used. The results of the study show that: there is a negative influence of peer support on academic achievement of 47% and a significance value of -0.062 < 0.05. Thus, it can be concluded that peer support affects academic achievement.